2021
DOI: 10.1007/s10531-021-02296-3
|View full text |Cite
|
Sign up to set email alerts
|

Sacred natural sites and biodiversity conservation: a systematic review

Abstract: Sacred natural sites (SNS) have gained recognition from conservationists, and are regarded as the oldest form of habitat protection in human history. Many case studies and literature reviews have been published on the subject. However, an updated and global-level synthesis on the effect of SNS on biodiversity conservation is still lacking. Here, we provide the first systematic review on SNS and biodiversity conservation, aiming to evaluate the effect of SNS across different: (i) continents; (ii) taxa; (iii) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 54 publications
(49 reference statements)
1
20
0
1
Order By: Relevance
“…In order to maintain the societal functions and provide a well-kept appearance of such kurgans, continuous extensive management is often provided by mowing and elimination of woody vegetation, which can also benefit grassland maintenance (Deák et al; 2020b). This phenomenon shows considerable similarities with the management of SNSs (sacred grooves, saint mountains, shrines, graveyards or church gardens), which can be found across the Globe and are traditionally extensively managed by the local populations for non-production purposes (Zannini et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In order to maintain the societal functions and provide a well-kept appearance of such kurgans, continuous extensive management is often provided by mowing and elimination of woody vegetation, which can also benefit grassland maintenance (Deák et al; 2020b). This phenomenon shows considerable similarities with the management of SNSs (sacred grooves, saint mountains, shrines, graveyards or church gardens), which can be found across the Globe and are traditionally extensively managed by the local populations for non-production purposes (Zannini et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…This pattern is especially important as kurgans with cultural protection are generally situated in heavily transformed, densely populated anthropogenic lowland landscapes, where grassland habitats are critically endangered (and 13% of kurgans outside PAs hold cultural values). In this respect, kurgans show similarity with sacred natural sites (SNSs) such as church yards, shrines or old cemeteries, which can also preserve parts of the former natural habitats in landscapes under a high anthropogenic pressure (Löki et al; 2019, Kowarik et al, 2016; Zannini et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, SNS are generally ignored in national and sub-national policies and actions for ecosystem management (Rutte 2011). Local studies on SNS can highlight the role of these sites in biodiversity conservation, provision of ecosystem services (Jackson and Ormsby 2017; Zannini et al 2021) and sustainable development (Verschuuren 2010).…”
Section: Policy Implicationsmentioning
confidence: 99%
“…SNS are defined as "areas of land or water holding special spiritual significance for people and communities" (Wild & McLeod, 2008) and are often regarded as the oldest form of habitat protection in human history. They can be viewed as forming a shadow network of unofficial PAs which conserves biodiversity, provides ecosystem services, and potentially strengthens the "official" protected network (Avtzis et al, 2018;Dudley et al, 2009;Frascaroli et al, 2019;Zannini et al, 2021). SNS are often found in association with ancient forest remnants (see e.g., Cardelús et al, 2013;Shakeri et al, 2021) and have been shown to locally halt or reduce deforestation (Campbell, 2004(Campbell, , 2005.…”
Section: Introductionmentioning
confidence: 99%